Infection control in the bronchoscopy suite: effective reprocessing and disinfection of reusable bronchoscopes. Issue 1 (10th January 2023) - Chhabria, Mamta S.; Maldonado, Fabien; Mehta, Atul C.
Abstract : Purpose of review: With advancements in technology, flexible bronchoscopes have become thinner in diameter and in need of more thorough reprocessing to prevent infection transmission than ever before. Many experienced bronchoscopists are not aware of the critical steps involved in effective bronchoscope reprocessing and we hope to bridge this gap by describing this process in detail. Recent findings: Bronchoscope reprocessing includes several distinct steps (precleaning, leak testing, manual cleaning, visual inspection, terminal reprocessing, rinsing and drying). Each step is comprehensive and needs to be carried out systematically by trained personnel. Failure of any step can lead to serious downstream events such as outbreaks and pseudo-outbreaks. Some experts now recommend sterilization when feasible, although high-level disinfection remains the minimum standard. We also will review some literature on the utility of borescopes, automated endoscope reprocessors and disposable bronchoscopes. Summary: Our article will focus on the most recent recommendations for effective reprocessing and disinfection of reusable bronchoscopes.